2018
DOI: 10.1002/admi.201800406
|View full text |Cite
|
Sign up to set email alerts
|

Thin, Porous, and Conductive Networks of Metal Nanoparticles through Electrochemical Welding on a Liquid Metal Template

Abstract: interfacial forces, [6][7][8] surface modifications, [9,10] as well as well-controlled external fields [11][12][13][14][15] have been adopted, which yield vast types of complex yet delicate particle structures with outstanding functionalities. By virtue of interfacial forces, fluid-interface-assisted self-assembly (or self-organization) has been proven to be a simple yet powerful method. [6,7,11,[16][17][18][19][20][21][22][23] Although self-assembled particle structures are stable at the confining template, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…22−27 It was reported that CO 2 was reduced to carbon species and copper oxide was reduced to copper phases on the surface of liquid metal at room temperature. 28,29 Moreover, a series of findings on biomimetic chromatic liquid-metal soft robots was disclosed recently. 30,31 Lightened by the above research studies, the discoloration effect of TMOs via liquid metal reduction was first expounded in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…22−27 It was reported that CO 2 was reduced to carbon species and copper oxide was reduced to copper phases on the surface of liquid metal at room temperature. 28,29 Moreover, a series of findings on biomimetic chromatic liquid-metal soft robots was disclosed recently. 30,31 Lightened by the above research studies, the discoloration effect of TMOs via liquid metal reduction was first expounded in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…Left: Reproduced with permission. [19] Copyright 2018, Wiley-VCH. (h) The schematic diagram of carbon dioxide fixation based on liquid metal.…”
Section: The Core-shell Structure Of Liquid Metalmentioning
confidence: 99%
“…Figure 7B described the synthesis of thin and conductive Cu-LM particles, which provided a general strategy for particle-based, interface-assisted fabrication. [19] Liquid metals provide a brand-new avenue for the catalytic synthesis and fixation of carbon materials in ambient circumstances. RTLMs can break the chemical bonds like CO, CN, and CH bonds in organic molecules at room temperature and reconstruct them into CC bonds of graphite-type.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
See 2 more Smart Citations